2017
DOI: 10.4055/cios.2017.9.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of Total Hip Arthroplasty between Patients with Ankylosing Spondylitis and Avascular Necrosis of the Femoral Head

Abstract: BackgroundThe objective of this study was to compare clinical and radiological outcomes of total hip arthroplasty (THA) between ankylosing spondylitis (AS) of the hip joint and avascular necrosis (AVN) of the femoral head.MethodsThirty patients (30 hips) underwent cementless THA for AS between 2003 and 2012. They were compared to 30 patients (30 hips) who underwent the same procedure for AVN of the femoral head. Each group was matched for age and gender, and both groups had similar preoperative demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…253 In contrast, cementless prostheses are preferred in AS patients, especially young patients, without significant morphological changes in the proximal femurs because this strategy can reduce the difficulty of future revisions while allowing bone ingrowth to enhance the durability of the implant. 258,259…”
Section: Treatments For Asmentioning
confidence: 99%
“…253 In contrast, cementless prostheses are preferred in AS patients, especially young patients, without significant morphological changes in the proximal femurs because this strategy can reduce the difficulty of future revisions while allowing bone ingrowth to enhance the durability of the implant. 258,259…”
Section: Treatments For Asmentioning
confidence: 99%
“…[ 1 2 3 ] Although studies of THA have normally demonstrated excellent results in greater than a 10-year follow-up period compared with that in patients with traumatic osteonecrosis of the femoral head (ONFH), those with nontraumatic ONFH tend to be younger and physically more active, and as a result, replaced hip joint may need to be revised. [ 1 3 4 5 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 There are several methods of surgical treatment of a femoral neck fracture and when the final treatment decision is made the following parameters should be taken into account: patient's age, activity level, bone tissue quality, additional diseases, type of fracture according to Garden and Pauwels classification as well as the related risk of complications. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%